Robot Corruption-Detector: Media Pembelajaran Antikorupsi untuk Anak - Sari, Ratna Candra; Fauziah, Puji Yanti; Ilyana, Sariyatul; Kurniawan, Erry Eka (Komisi Pemberantasan Korupsi, 2020)
This study aims to develop an anti-corruption learning media called